The Correlation between Semen Parameters in Processed and Unprocessed Semen with Pregnancy Rate in Intrauterine Insemination in the Treatment of Male Factor Infertility - Dadkhah, Farid; Nahabidian, Aram; Ahmadi, G (Urology Journal, 2009)
Purpose: Our aims were to determine the relation of semen parameters in processed and unprocessed semen samples with pregnancy rate in intrauterine insemination (IUI) in the treatment of male factor infertility. Materials and Methods: In a quasi experimental study, 412 couples with male factor infertility were studied. To treat male factor infertility, 561 IUI cycles were done. Results: Total pregnancy rate was 7.84% (44 in 561) per cycle. There was an inverse relationship between pregnancy rate and duration of infertility. Total sperm count after processing was higher in pregnant cycles than in non-pregnant ones (P < 0.05). The mean total motile sperms after processing for pregnant and non-pregnant cycles was 72.2 Â± 78.8 and 53.2 Â± 54.3, respectively (P < 0.05). Conclusion: IUI is a valuable method for the treatment of male factor infertility. The higher number of sperms, total motile sperms and IUI sessions, and lower duration of infertility, all have a positive relationship with pregnancy rate.